FTA Highlight No.2 – Tree Seed and Seedling Systems for Resilience and Productivity - Graudal, L.; Lillesø, Jens-Peter B.; Dawson, Ian K.; Abiyu, A.; Roshetko, J.M.; Nyoka, I.; Tsobeng, A.; Kindt, R.; Pedercini, F.; Moestrup, S.; Jalonen, R.; Thomas, E.; et al. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The work of the CGIAR Research Program on Forests, Trees and Agroforestry (FTA) on tree seed systems — the authors’ shorthand for the means through which growers obtain access to tree-planting materials, either seeds or seedlings — has sought to address significant constraints in the diversity and genetic quality of the tree seeds and seedlings that are being supplied. These concerns are exacerbated by an increase in demand for germplasm to meet huge global forest landscape restoration commitments and other tree-planting targets. Over the last decade, FTA has worked on twin concerns in this regard: first, how to make available quality tree-planting material; and second, how to ensure that tree seeds and seedlings are planted in the right places for the right purposes. It has addressed availability through building stakeholder partnerships and model tree seed systems; delivering improved “orphan” (under-researched) tree crops through supporting breeding and its impact; mainstreaming food trees through nurseries; conserving and making available diverse tree germplasm to support delivery and use; and developing policies to support the effective supply of tree seeds and seedlings. It has supported better decision making through building information platforms to support tree-planting choices and tree seed system operations; designing maps to guide tree seed and seedling distribution that is suited to current and predicted future climatic conditions; and releasing statistical packages to guide appropriate tree planting and assess the impacts of this planting in terms of benefits such as additional carbon sequestered and extra soil protected. This work is the foundation of local and global economic and environmental benefits of huge significance. It supports climate change mitigation and adaptation, restores landscapes and conserves biodiversity, and provides healthy foods and other products for local and global communities. This publication focuses on FTA’s work in these areas. Future directions for work identified include a closer analysis of the relative importance of supply side versus demand-side measures for mainstreaming improved tree genetic materials by growers; working with investors to improve tree seed quality at the project design stage of tree-planting programmes; and scaling up existing tree seed systems experience to burgeoning forest landscape restoration and broader tree planting initiatives. This scaling up will involve further engagement with major global initiatives such as the Bonn Challenge, the UN Decade on Ecosystem Restoration 2021–2030, and the Global Plan of Action on Forest Genetic Resources.